Vitamin C deficiency in critically ill COVID-19 patients admitted to intensive care unit - Chiscano-Camón, Luis; Ruiz-Rodriguez, Juan Carlos; Plata-Menchaca, Erika P.; Martin, Laura; Bajaña, Ivan; Martin-Rodríguez, Cristina; Palmada, Clara; Ferrer-Costa, Roser; Camos, Silvia; Villena-Ortiz, Yolanda; Ribas, Vicent; Ruiz-Sanmartin, Adolf; et al. (Frontiers in Medicine, 2023)
Objectives: To determine vitamin C plasma kinetics, through the measurement of vitamin C plasma concentrations, in critically ill Coronavirus infectious disease 2019 (COVID-19) patients, identifying eventually the onset of vitamin C deficiency. Design: Prospective, observational, single-center study. Setting: Intensive Care Unit (ICU), Vall d’Hebron University Hospital, Barcelona. Study period from November 12th, 2020, to February 24th, 2021. Patients: Patients who had a severe hypoxemic acute respiratory failure due to COVID-19 were included. Interventions: Plasma vitamin C concentrations were measured on days 1, 5, and 10 of ICU admission. There were no vitamin C enteral nor parenteral supplementation. The supportive treatment was performed following the standard of care or acute respiratory distress syndrome (ARDS) patients. Measurement: Plasma vitamin C concentrations were analyzed using an ultra-performance liquid chromatography (UPLC) system with a photodiode array detector (wavelength set to 245 nm). We categorized plasmatic levels of vitamin C as follows: undetectable: < 1,5 mg/L, deficiency: <2 mg/L. Low plasma concentrations: 2 - 5 mg/L; normal plasma concentration: > 5 mg/L). Main Results: Forty-three patients were included (65% men; mean age 62 ± 10 years). The median Sequential Organ Failure Assessment (SOFA) score was 3 (1-4), and the Acute Physiology and Chronic Health disease Classification System (APACHE II) score was 13 (10 - 22). Five patients had shock. Bacterial coinfection was documented in 7 patients (16%). Initially all patients required high-flow oxygen therapy, and 23 (53%) further needed invasive mechanical ventilation during 21 (± 10) days. The worst PaO2/FIO2 registered was 93 (± 29). ICU and hospital survival were 77% and 74%, respectively. Low or undetectable levels remained constant throughout the study period in the vast majority of patients. Conclusions: This observational study showed vitamin C plasma levels were undetectable on ICU admission in 86% of patients with acute respiratory failure due to COVID-19 pneumonia requiring respiratory support. This finding remained consistent throughout the study period.